2022
DOI: 10.1161/jaha.121.022697
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Coronary Artery Disease Consortium Model and the Coronary Artery Calcium Score in Predicting Obstructive Coronary Artery Disease in a Symptomatic Mixed Asian Cohort

Abstract: Background The utility of a given pretest probability score in predicting obstructive coronary artery disease (CAD) is population dependent. Previous studies investigating the additive value of coronary artery calcium (CAC) on pretest probability scores were predominantly limited to Western populations. This retrospective study seeks to evaluate the CAD Consortium (CAD2) model in a mixed Asian cohort within Singapore with stable chest pain and to evaluate the incremental value of CAC in predicting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 53 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…In high CACS and CAD, 21,22 and it has now become a reliable method to detect and quantitatively evaluate coronary artery calcification in patients to screen for CAD risk. 23,24 Furthermore, CACS can provide a long-term and independent prognosis for the clinical risk of CAD events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In high CACS and CAD, 21,22 and it has now become a reliable method to detect and quantitatively evaluate coronary artery calcification in patients to screen for CAD risk. 23,24 Furthermore, CACS can provide a long-term and independent prognosis for the clinical risk of CAD events.…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, Agatston developed a calculation method to evaluate the burden of coronary atherosclerosis 20 by evaluation of CACS in coronary arteries, called the Agatston score, which is measured by CACT. Previous studies have demonstrated a correlation between high CACS and CAD, 21,22 and it has now become a reliable method to detect and quantitatively evaluate coronary artery calcification in patients to screen for CAD risk 23,24 . Furthermore, CACS can provide a long‐term and independent prognosis for the clinical risk of CAD events 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 10 Given the clinical utility of the Agatston coronary artery calcium score (CACS) as a gatekeeper to further testing, 11 it has been incorporated in PTP tools such as the CAD2 (CACS) model and the CACS‐weighted clinical likelihood model (CACS‐CL), resulting in its guideline recommendation. 1 , 8 , 12 , 13 …”
mentioning
confidence: 99%
“…Tools derived and initially well validated in Western cohorts have performed less well in Asian contexts. 13 , 14 , 15 Singapore has a population comprising 3 major Asian ethnicities (Chinese [74.3%], Malay [13.5%], and Indian [9.0%]) that provide a unique snapshot of the genetic diversity across East, Southeast, and South Asia. 16 , 17 There is a paucity of evidence comparing contemporary Western tools to a model in the Asian context.…”
mentioning
confidence: 99%
See 1 more Smart Citation